1994
DOI: 10.1093/oxfordjournals.annonc.a058908
|View full text |Cite
|
Sign up to set email alerts
|

Docetaxel (Taxotere®): An active drug for the treatment of patients with advanced squamous cell carcinoma of the head and neck

Abstract: Docetaxel is an active drug in patients with advanced squamous cell carcinoma of the head and neck.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
93
1
3

Year Published

2001
2001
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 221 publications
(99 citation statements)
references
References 12 publications
2
93
1
3
Order By: Relevance
“…In three phase II studies (Table 1), single-agent docetaxel (100 mg m À2 ) administered on day 1 every 3 weeks produced response rates ranging from 21 to 42% (Catimel et al, 1994;Dreyfuss et al, 1996;Couteau et al, 1999). As expected, grade III -IV neutropenia was the principal toxicity in these studies.…”
Section: Potential Of Docetaxel In Scchnmentioning
confidence: 52%
See 1 more Smart Citation
“…In three phase II studies (Table 1), single-agent docetaxel (100 mg m À2 ) administered on day 1 every 3 weeks produced response rates ranging from 21 to 42% (Catimel et al, 1994;Dreyfuss et al, 1996;Couteau et al, 1999). As expected, grade III -IV neutropenia was the principal toxicity in these studies.…”
Section: Potential Of Docetaxel In Scchnmentioning
confidence: 52%
“…Perhaps the most promising agents have been the taxanes. In particular, the taxane docetaxel has demonstrated significant single-agent activity in recurrent SCCHN (Catimel et al, 1994;Dreyfuss et al, 1996;Couteau et al, 1999). Docetaxel is similar to paclitaxel with respect to its general mechanism of action (tubulin stabilization and cell cycle arrest), and the two share a number of pharmacological characteristics (Colevas and Posner, 2001).…”
mentioning
confidence: 99%
“…A phase II clinical trial of docetaxel monotherapy for the treatment of advanced/recurrent ESCC reported a response rate of 20.4%. These findings indicate that docetaxel may be a useful chemotherapeutic agent for the treatment of ESCC (9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 76%
“…The utility of docetaxel for head and neck disease has been confirmed in the clinic. Docetaxel has demonstrated activity in the setting of advanced metastatic disease, [5][6][7] and is feasible in combination with concurrent daily radiotherapy. 8 -10 The current trial builds on these previous reports by using two complementary clinical strategies.…”
Section: Conclusion This Regimen Was Feasiblementioning
confidence: 99%